1995
DOI: 10.1097/00004032-199506000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Curve for Chromosome Translocations Measured in Human Lymphocytes Exposed to 60Co Gamma Rays

Abstract: Chromosome painting was employed to measure frequencies of reciprocal translocations in human lymphocytes induced by 60Co gamma rays, with emphasis on low doses. Translocations and dicentrics were distinguished by use of a pan-centromeric probe. A total of 41,151 metaphases were analyzed at doses below 0.2 Gy. The linear "take-off" slope of the linear-quadratic dose-response curve for translocations, i.e., the alpha coefficient, was measured to be 0.023 +/- 0.005 translocations per cell per Gy. This alpha coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…For example, 4 Gy of 60 Co gamma irradiation generated on average one translocation per cell (9). Therefore, to determine whether the delay in mitotic chromosome condensation chromosomes in our irradiated primary blood lymphocytes represented interchromosomal translocations and to estimate the frequency of interchromosomal translocations in these irradiated populations, we analyzed mitotic spreads using FISH with five different whole chromosome painting probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 4 Gy of 60 Co gamma irradiation generated on average one translocation per cell (9). Therefore, to determine whether the delay in mitotic chromosome condensation chromosomes in our irradiated primary blood lymphocytes represented interchromosomal translocations and to estimate the frequency of interchromosomal translocations in these irradiated populations, we analyzed mitotic spreads using FISH with five different whole chromosome painting probes.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the data presented here indicate that this abnormal phenotype is regulated in cis-, and, therefore, may be under genetic control. Ionizing radiation is expected to generate between 20 and 40 DNA double-strand breaks per cell per Gy (25), whereas producing only 0.25 to 0.5 interchromosomal translocations per cell per Gy (9), indicating that the majority of double-strand breaks are repaired without the generation of interchromosomal translocations or the delay in replication timing/ delay in mitotic chromosome condensation phenotype. Therefore, because we found that the majority of delay in mitotic chromosome condensation chromosomes induced by ionizing radiation were in fact interchromosomal translocations, but only 5% of interchromosomal translocations displayed delay in mitotic chromosome condensation, our data indicate that only a subset of the double-strand breaks that resolve into interchromosomal translocations produce the delay in replication timing/delay in mitotic chromosome condensation phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This is actually possible in some cases. For example, the measurement of stable translocations in chromosomes of circulating lymphocytes can be performed using the technique of chromosome painting (Lucas et al 1995). This technique has a sensitivity of about 100 mGy, but is time consuming and expensive; to date the technique has only been used successfully in a small number of cases.…”
Section: Methods Of Dose Reconstructionmentioning
confidence: 99%
“…This technology employs fluorescence in situ hybridization (FISH) with whole chromosome probes to rapidly and accurately detect chromosome abnormalities such as stable reciprocal translocations in human cells. The development of this technology began at LLNL during the early 1980's (Pinkel et al 1986) and has now developed into the method of choice world-wide for the detection of chromosome translocations in humans (e.g., see Lucas et al 1992a;Nakano et al 1993;Bauchinger et al 1993;Straume et al 1995;National Research Council 1995).…”
Section: Introductionmentioning
confidence: 99%